Dietary supplementation of Bacillus-based probiotics on the growth performance, gut morphology, intestinal microbiota and immune response in low biosecurity broiler chickens. (December 2021) - Arif, Mohammad; Akteruzzaman, Md.; Tuhin-Al-Ferdous,; Islam, Sk Shaheenur; Das, Bidhan Chandra; Siddique, Mahbubul Pratik; Kabir, S. M. Lutful
Abstract: A feeding trial was conducted to evaluate the effects of Bacillus -based probiotics on growth performance, intestinal histo-morphology, gut microbial population and immune response in broilers. A total of 2000 Hubbard Classic day-old chicks were randomly enrolled in four experimental groups and 4 replicates of 500 birds in each group, and reared for 35 days under a low- level of biosecurity measures. The trial groups were assigned treatment-1 (T1): basal diet(control), treatment-2 (T2): basal diet plus Bacillus licheniformis (DSM17236), treatment-3 (T3): basal diet plus Bacillus subtilis (PB6), and treatment-4 (T4) basal diet plus 4% Flavomycin. All four groups were fed with maize-soybean based prepared feeds (starter, grower and finisher). Dietary inclusion of B. licheniformis significantly improved body weight gain and lessened FCR in T2 compared to other groups ( p < 0.05). Probiotics increased the population of Bacillus spp. and decreased the population of Clostrium perfringens, Salmonella spp. and Escherichia coli in the jejunum and ileum in broiler birds on day 21 and 35 ( p < 0.05). The highest antibody production was observed in B. licheniformis treated group (T2) compared to other probiotic treated group (T1). Taken together, the study findings suggest that B. licheniformis probiotics could be used as a feasible alternative to antimicrobials in the broiler production considering beneficial impacts at low biosecurity broiler farms.